The Power of Petition in Altering the Postal Routes of Rural Ontario: A Case Study from Haliburton - Martinello, Christopher (Ontario History, 2024)
In the late nineteenth-century, rural post offices linked settlers to the rest of Canada and, indeed, the world. But such offices also allowed them to petition the Post Office itself particularly when it came to influencing the mail routes connecting remote hamlets to each other. This article examines the petitions submitted by settlers in the Haliburton region of Ontario in attempts to affect mail routes. They used the changing significance of villages in Haliburton County as their main motivation when petitioning. In areas without railroads, settlers used the poor state of colonization roads and local business interests to strengthen their arguments for change. The records also reveal that rural postmasters contended against each other to ameliorate their own hamlets. Understanding the social forces that influenced mail routes can enhance our perspective of the changing nature and role of the Post Office in the late nineteenth century.